Study on Coercivity-Stress Relationship of X80 Steel under Biaxial Stress - Shulu Feng; Zhijiu Ai; Jian Liu; Jiayi He; Yukun Li; Qifeng Peng; Chengkun Li (Advances in Materials Science and Engineering)
Buried pipelines are prone to deformation under surface displacement, pressure occupation, and/or other actions, resulting in stress concentration. Conducting regular stress detection is an important approach to reducing pipeline accidents. This study performed experiments on measuring the coercivity stress of X80 steel, the most commonly used material for high-pressure large-diameter gas transmission pipelines. The coercivity of the specimen under different stress combinations was measured using the DC-driven coercive force measurement system, and the variation of coercive force with biaxial stress was also analyzed. The modified coercive force-stress expression of the generalized Hooke’s law was proposed; the model for the coercive force-stress relationship of X80 steel under the biaxial stress state was established based on this expression. The study indicates that the coercive force method is reliable for accurately measuring the stress of pipeline steel and evaluating the safety margin of in-service pipelines.